Biocompatible ruthenium polypyridyl complexes as efficient radiosensitizers. Issue 13 (6th March 2019) - Xiong, Zushuang; Zhong, Jing-Xiang; Zhao, Zhennan; Chen, Tianfeng
Abstract : A biocompatible ruthenium polypyridyl complex has been rationally designed, which could self-assemble into nanoparticles in aqueous solution to enhance the solubility and biocompatibility, and could synergistically realize simultaneous cancer chemo-radiotherapy. Abstract : A biocompatible ruthenium polypyridyl complex has been rationally designed and synthesized, which self-assembles into nanoparticles in aqueous solution to enhance the water solubility and biocompatibility. When activated by X-rays, the nanostructure synergistically triggers ROS overproduction in cancer cells to induce mitochondrial dysfunction and cell cycle arrest, thus realizing simultaneous chemo-radiotherapy.